Pandangan Hakim tentang Pengasuhan Bersama dalam Hadhanah Pasca Perceraian - Sembiring, Muhammad Andyansyah; Turnip, Ibnu Radwan Siddik (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study examines the views of judges at the Religious Court of Medan regarding the concept of shared parenting after divorce. The issue arises because a sole custody pattern often leads one parent to evade responsibility, thereby disadvantaging the child. The objective of this research is to determine whether shared parenting can serve as a more appropriate alternative in ensuring the best interests of the child. The study employs a normative–empirical method with approaches drawn from sociology of law, legal psychology, and legal studies. Primary data were obtained through in-depth interviews with judges of the Religious Court of Medan, while secondary data were derived from statutory regulations, the Compilation of Islamic Law, court decisions, and relevant legal literature. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that judges generally consider shared parenting to be consistent with the principles of justice and the best interests of the child, as it allows the involvement of both parents. However, its implementation remains limited due to the absence of explicit normative regulation, resulting in reliance on judicial discretion or the agreement of the parties. In conclusion, shared parenting has gained substantive acceptance among judges and holds potential for further development within Islamic family law in Indonesia, supported by regulatory frameworks or technical guidelines.